Estudo do comportamento à fadiga em ferro fundido nodular austemperado (ADI) sujeito a carregamentos de amplitude variável - Jose Felipe Dias (2006)
An investigation was carried out to verify the influence of austempering temperature and time on the fatigue behavior of Austempered Ductile Iron (ADI), under variable amplitude loading. ADI specimens with 0,5% of copper and of nickel were used in fatigue propagation, rotating and reciprocating bending fatigue tests. The fatigue life results under variable amplitude loading have been analyzed by linear and double lineardamage rules. The fatigue crack growth rate was estimated by Pariss law. Samples were machined from 13 mm casting blocks. Three set of samples were prepared, all of them austenitized at 900°C for 1,5 hour and then austempered at two different temperatures and three different times: the first set was austempered at 360°C for 1,5 hours; the second at 360°C for 0,6 hour and the third at 300°C for 2,5 hours. The material was characterized and analyzed by means of optical and scanning electron microscopy, X-Ray diffraction and mechanical tests. Unnotched samples were tested in rotating bending fatigue using different cyclic stress amplitudes. The reciprocating bending fatigue tests were performed using strain control. Fatigue crack growth tests were performed under constant and variable amplitude cyclic stress intensity. The materials austempered at 360°C showed greater rates of austenite and ductility, and smaller tensile stress and hardness than the materials austempered at 300°C. The carbon contents in the austenite in the second set were smaller than the contents in the first set. Among the observations made, the most important ones are: (i) the materialsaustempered at 360°C showed longer fatigue live than the ones austempered at 300°C, under both constant and variable amplitude loading, near 500 MPa; (ii) materials treated at 360°C, showed smaller crack growth rate than those austempered at 300°C; (iii) *bigger rates of austenite and smaller rates of carbon provided the material with biggernucleation fatigue resistance; (iv) the rate of crack growth of the material in the second set, under constant cyclic stress intensity factor was smaller than under variable stress; (v) the linear and double linear damage rules did not offer satisfactory results in predicting fatigue life of ADI; (vi) beneficial effects from the first set were observed in the second set only when stress amplitude beyond the fatigue limit was applied.